A Review of Researches on Employee’s Trait Mindfulness - Yu, Mengtong (Transactions on Economics, Business and Management Research, 2024)
Mindfulness is an ancient concept derived from eastern Buddhism. Mindfulness is defined as "an acceptable attention and awareness of current events and experiences" in workplace studies. In recent years, western empirical studies have found that mindfulness has a positive impact on workplace employees’ organizational citizenship behavior, work performance, etc. Mindfulness training has been applied in some well-known companies and received favorable comments from employees. Mindfulness research has great potential in the future in the workplace. However, this kind of research has not attracted much attention in China.Based on the existing research results abroad, this paper introduces the origin, concept and measurement of mindfulness. Then from the antecedent variables, outcome variables and mindfulness as moderating variables, the empirical research and theoretical exploration results of workplace mindfulness are summarized. On this basis, the framework chart of the existing research results is constructed, and the research prospects are put forward for the deficiencies in antecedent variables, outcome variables, moderating effect, measurement and research methods, and localization research.